2014
DOI: 10.1177/1934578x1400900531
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Melissa officinalis Leaves Determined by Plant Age

Abstract: The present study investigated changes in the content and chemical composition of the essential oil extracted by hydrodistillation from air-dried Melissa officinalis L. (lemon balm) leaves in the first and second year of plant growth. The lemon balm oil was analysed by GC-MS and GC-FID. The presence of 106 compounds, representing 100% of the oil constituents, was determined in the oil. The predominant components were geranial (45.2% and 45.1%) and neral (32.8% and 33.8%); their proportions in the examined samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…3). Research on lemon balm [Nurzyńska-Wierdak et al 2014] and lemon grass [Rocha et al 2014] shows that plant age may cause differences in the content of essential oil to a lesser extent than in its chemical composition. Santos et al [2012], on the other hand, demonstrated that in the case of harvest of Alpinia zerumbet (Zingiberaceae) leaves, with increasing age there is a significant increase in plant biomass as well as in essential oil content and yield.…”
Section: Resultsmentioning
confidence: 99%
“…3). Research on lemon balm [Nurzyńska-Wierdak et al 2014] and lemon grass [Rocha et al 2014] shows that plant age may cause differences in the content of essential oil to a lesser extent than in its chemical composition. Santos et al [2012], on the other hand, demonstrated that in the case of harvest of Alpinia zerumbet (Zingiberaceae) leaves, with increasing age there is a significant increase in plant biomass as well as in essential oil content and yield.…”
Section: Resultsmentioning
confidence: 99%
“…As listed in Table 2 , nine metabolites were found to be significantly decreased in the home collected alcoholic fecal samples. Of these, caryophyllene, a widely dispersed phytochemical [ 44 – 46 ], is a well characterized agonist of the cannabinoid receptor 2. Interestingly, the association of caryophyllene with the cannabinoid receptor 2 has been shown to reduce voluntary alcohol intake in mice and as such the receptor has been suggested as a target for the pharmaceutical intervention of alcoholism [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Iran, the main components were (E)-citral (37.2%), neral (23.9%) and citronellal (20.3%) [21] . However, the age of lemon balm plants affected the concentration of other constituents and the proportions of the following compounds were subject to especially high fluctuations: citronellal (8.7% and 0.4%), geraniol (trace amounts and 0.6%), and geranyl acetate (0.5% and 3.0%), as well as, among others, isogeranial, E-caryophyllene, caryophyllene oxide, germacrene D, and carvacrol [22] .…”
Section: Discussionmentioning
confidence: 98%
“…Each microorganism stock was suspended in Mueller-Hinton (MH) broth and then incubated at 37 C for [18][19][20][21][22][23][24] h. The overnight cultures were diluted and adjusted in order to get a density of 10 8 CFU/mL (0.5 McFarland turbidity standard). They were flood-inoculated onto the surface of MH agar and 6 mm diameter, and sterile filter discs of Whatman paper No.…”
Section: Microorganisms Includedmentioning
confidence: 99%